Current Agricultu ral and Environmental Policies in Benin Republic - Dayou, Ephrème Dossavi; Zokpodo, Koessi Lié Barnabé; MONTCHO, Marthe; AJAV, Emmanuel; Bamgboye, Isaac A; Glèlè Kakaï, Romain L. (My University, 2020)
The need to feed the population growth conducts to the development of material intensive production systems in many countries. However the absence of adequate policies has adverse consequences on the environment and the performance of the agricultural and rural s ectors. Benin Republic, through its Strategic Plan for Agricultural Sector Development (PSDSA) focuses on improving food and nutrition security, improving farm level income and building resilience to climate change within the Government Action Plan (PAG Bénin Révélé) 2016 2021. The aim of this study is to analyze the current agricultural policies and its link with the current environmental policies in Benin Republic. The data from Ministries and Structures in charge of Agriculture, Environment, health and Human being were used. Reports from some international organizations such as FAO, PNUD and FIDA were also used. It is observed and planed an increase in cultivation a rea, all crops yields and crops production from 2016 to 2021. That will involve the more use of agricultural machinery, fertilizers and pesticides. Added to the current environment challenges, it appears the risk of soil degradation, deforestation, water a nd air pollution, then global impact on the environment when this plan will be implemented. It is right that some Environment Impact Assessment (EIA) are purposed for many of the action s . However, these EIA are sometime neglected and sacrificed for the profitability of agricultural production. To achieve this agricultural goal without affect the environment, the respect of the adequate law and EIA for each single activity becomes necessary.
Keywords: food production policy; natural resource management policy; environmental degradation; sustainable; development; Benin Republic